Magneto-optic ellipsometry characterization of Co and SmCo thin films - Tkachenko, Volodymyr; Abbate, Giancarlo; Marino, Antigone (Photonics Letters of Poland, 2017)
Magneto-optic ellipsometry in the longitudinal Kerr configuration was performed to determine the complex permittivity tensor of the Co and SmCo thin films within the spectral range from 400nm to 1000nm. The Co film was a middle layer in a Au/Co/Au trilayer structure. Magneto-optical response was analyzed in terms of Mueller matrix elements. Reduced magneto-optical response of the Co layer is explained by influence of the gold top layer of the trilayer structure. Full Text: PDF References M. Mansuripur, The Physical Principles of Magneto Optical Recording (Cambridge, Cambridge University Press, 1995). CrossRef B. Sepúlveda, A. Calle, L.M. Lechuga, G. Armelles, "Highly sensitive detection of biomolecules with the magneto-optic surface-plasmon-resonance sensor", Opt. Lett. 31, 1085 (2006). CrossRef D. Regatos et al., "Au/Fe/Au multilayer transducers for magneto-optic surface plasmon resonance sensing", J.Appl.Phys. 108, 054502 (2010). CrossRef D. Regatos, B. Sepúlveda, D. Farina, L.G. Carrascosa, L.M. Lechuga, "Suitable combination of noble/ferromagnetic metal multilayers for enhanced magneto-plasmonic biosensing", Opt. Express 19, 8336 (2011). CrossRef G. Armelle et al., "Localized surface plasmon resonance effects on the magneto-optical activity of continuous Au/Co/Au trilayers", Opt. Express 16, 16104 (2008). CrossRef C. Hermann, "Surface-enhanced magneto-optics in metallic multilayer films", Phys. Rev. B 64, 235422 (2001). CrossRef J. B. González-Díaz et al., "Surface-magnetoplasmon nonreciprocity effects in noble-metal/ferromagnetic heterostructures", Phys. Rev. B 76, 153402 (2007). CrossRef V. V. Temnov et al., "Active magneto-plasmonics in hybrid metal?ferromagnet structures", Nat. Photonics 4(2), 107 (2010). CrossRef A. Berger, M. R. Pufall, "Generalized magneto-optical ellipsometry", Appl. Phys. Lett. 71, 965 (1997). CrossRef R. Rauer, G. Neuber, J. Kunze, J. Backstrom, M. Rubhausen, "Temperature-dependent spectral generalized magneto-optical ellipsometry for ferromagnetic compounds", Rev. Sci. Instrum. 76, 023910 (2005). CrossRef K. Mok, N. Du, H. Schmidt, "Vector-magneto-optical generalized ellipsometry", Rev. Sci. Instrum. 82, 033112 (2011). CrossRef W.A. McGahan, J.A. Woollam, "Magnetooptics of multilayer systems", Appl. Phys. Commun. 9, 1 (1989). D.P. Kumah et al., "Optimizing the planar structure of (1 1 1) Au/Co/Au trilayers", J. Phys. D: Appl. Phys. 40, 2699 (2007). CrossRef L. Alocca et al., "Laser deposition of SmCo thin film and coating on different substrates", Phys. Scr. 78, 058114 (2008). CrossRef H.G. Tompkins, E.A. Irene, Handbook of Ellipsometry (Norwich, William Andrew, 2005). CrossRef G. Abbate et al., "Optical characterization of liquid crystals by combined ellipsometry and half-leaky-guided-mode spectroscopy in the visible-near infrared range", J. Appl. Phys. 101, 073105 (2007). CrossRef Y.V. Knyazev, M.N. Noskov, "OPTICAL PROPERTIES OF GADOLINIUM, SAMARIUM, AND DYSPROSIUM IN THE SPECTRAL RANGE 1.13 TO 3.96 eV.", Phys. Met. Metallogr. 30, 230 (1970).